Breath Biomarkers of Whole-body Gamma Irradiation in the Göttingen Minipig. Issue 5 (May 2015) - Phillips, Michael; Cataneo, Renee N.; Chaturvedi, Anirudh; Kaplan, Peter D.; Libardoni, Mark; Mundada, Mayur; Patel, Urvish; Thrall, Karla D.; Zhang, Xiang
<x xml:space="preserve">Abstract</x> Abstract There is widespread interest in the development of tools to estimate radiation exposures. Exhaled breath provides a novel matrix for assessing biomarkers that could be correlated with exposures. The use of exhaled breath for estimating radiation exposure is warranted, as studies have shown that external exposure to ionizing radiation causes oxidative stress that accelerates lipid peroxidation of polyunsaturated fatty acids, liberating alkanes and alkane metabolites that are excreted in the breath as volatile organic compounds (VOCs). As a proof of principle study, small groups (n = 4) of Göttingen minipigs were whole-body irradiated with gamma rays delivered by a 60Co source at absorbed doses of 0, 0.25, 0.5, 0.75, 1, 1.25, 2, and 4 Gy. Additional groups (n = 4) were treated with lipopolysaccharide (LPS) or granulocyte colony stimulating factor (G-CSF), with and without concurrent 60Co exposure, at an absorbed dose of 1 Gy. Breath and background air VOC samples were collected on days −3, −2, −1, 0 pre-irradiation, then at 0.25, 24, 48, 72, and 168 h post-irradiation. VOCs were analyzed by automated thermal desorption with two-dimensional gas chromatography and time-of-flight mass spectrometry (ATD GCxGC TOF MS). The results show significant changes in 58 breath VOCs post-irradiation, mainly consisting of methylated and other derivatives of alkanes, alkenes, and benzene. Using a multivariate combination of these VOCs, a radiation response function was constructed, which was significantly elevated at 15 min post irradiation and remained elevated throughout the study (to 168 h post irradiation). As a binary test of radiation absorbed doses ≥ 0.25 Gy, the radiation response function distinguished irradiated animals from shams (0 Gy) with 83–84% accuracy. A randomly derived radiation response function was robust: When half of the biomarkers were removed, accuracy was 75%. An optimally derived function with two biomarkers was 82% accurate. As a binary test of radiation absorbed doses ≥ 0.5 Gy, the radiation response function identified irradiated animals with an accuracy of 87% at 15 min post irradiation and 75.5% at 168 h post irradiation. Treatment with LPS and G-CSF did not affect the radiation response function. This proof-of-principle study supports the hypothesis that breath VOCs may be used for estimating radiation exposures. Further studies will be required to validate the sensitivity and specificity of these potential biomarkers.